A Taxonomic Study of Macro-and Micro Morphological Features of Fruits and Seeds Cultivars of the Species Belonging to the Genus Morus L. (Moraceae) Cultivated in the North of Iraq - Raad Al-Badrany; Aamer Al-Mathidy (College of Education for Pure Sciences, 2020)
The present work deal with the morphological characters of the fruits and seed of the cultivars belonging to the species Morus alba L. Namely ("Beautiful Day", "Big White", "Rease", "Greece", "Pearl", "Border Sweet", "Pendula"); Morus latifolia Poir ("Kokuse Korean"); Morus rubra L. ("Amarah"); Morus nigra ("Shami"); Morus macroura Miq ("King White"); "Dwarf" and Morus hybrid ("Tice", "Wellington") Which cultirated in North of Iraq. The study includes the characters of the fruits (Shape, Color, Dimension, Size, Number of the fruitlet in the fruit) and the characters of the seeds (Shape, Color, Dimension, Number of the seeds in the fruit, and surface ornamentation). The results of some morphological characteristic of the fruits and seeds examined by light microscope (L.M), in addition to the surface ornamentation of the seeds examined by scanning electron microscope (SEM). Showed five type of the surface ornamentation (Reticulate, Muricate, Foreate undulate, Polygonal, and Ruminate) for cultivars species studied, showed that importance value in the separation between the cultivars of the species studied belonging to the genus Morus L.